A monetary interpretation of the post-1965 inflation in the United States - D.I. FAND (PSL Quarterly Review, 2014)
One important assumption of non-monetary inflation theories is that the monetary theory of the “new economics” and the stabilisation theories followed since 1965 are basically sound. Accordingly, the ensuing inflation must be due to errors of implementation, whether committed by politicians or by the technicians. The implication of these theories is that the failure of the June 1968 tax action to stop the inflationary pressures thus far is somehow due to implementation errors, but does not reflect on the monetary actions taken since 1965. The present paper focuses on the monetary aspects of post-1965 inflation in the U.S.: Are the non-monetary inflation theories essentially correct in viewing the inflationary pressures in 1968 and 1969 as consequences of implementation errors committed in 1965 or 1966, at the time of the Vietnam escalation, and compounded by the delay in passing the surtax in 1967; or are they abstracting from the major factor in the current inflation - the extraordinary high rates of growth in the monetary aggregates since 1965, and especially the pronounced rise in the rate of monetary acceleration after the tax action in June 1968.